Smartphone Sensor-based Development and Implementation of a Remotely Controlled Robot Arm - Salah, Wael A.; Sneineh, Anees Abu; Shabaneh, Arafat A. A. (Journal of Robotics and Control (JRC), 2024)
As a result of advances in both technology and science, it is now possible to carry out essential processes such as lifting objects and moving them by remote control of an arm. In this sense, it is much easier for a person to engage in potentially dangerous activities without running the risk of getting hurt. This article presents the development and design of a robot arm that is controlled by a smartphone device using gyroscope sensors integrated inside. Smartphones with built-in gyroscope sensors are used to operate robot arms in a flexible and affordable manner. The robot arm's movement is effectively controlled by the gyroscope sensors, which include proximity, orientation, and accelerometer sensors, to get it to the required position. The developed prototype found to capable of handling a variety of objects with a smooth movement and transporting them based on the movement of a mobile phone. The control of the arm imitates the movements of a human being, which results in the reduction of the amount of time and effort required by a person to carry out a certain process.